Prevalence and factors associated with the depressive symptoms in rural and urban Mexican older adults: evidence from the Mexican Health and Aging Study 2018 - Alvaro García-Pérez; Alvaro Edgar González-Aragón Pineda; Bayron Alexander Sandoval-Bonilla; Luis Pablo Cruz-Hervert (Instituto Nacional de Salud Pública, 2022)
Objective. To determine the prevalence and factors related to depressive symptoms in older Mexican adults in urban and rural areas. Materials and methods. Cross-sectional study. We examined older adults from a sample taken from the Mexican Health and Aging Study (MHAS-2018). 14 230 older Mexicans were screened for self-reported depressive symptoms. Results. The prevalence of depressive symptoms was 29.8% (33.4% rural vs. 28.9% urban). In the rural and urban population, the probability of a high prevalence of depressive symptoms was higher in older adults with multimorbidity ≥3, severe pain, and fair/poor SRH. Only in the urban population the prevalence of depressive symptoms increased with lower schooling. Conclusion. Identification of the factors related to depressive symptoms may help healthcare professionals provide better treatment for specific groups in the population.